Effect of body mass index on ulnar nerve conduction velocity, ulnar neuropathy at the elbow, and carpal tunnel syndrome - Landau, Mark E.; Barner, Kristen C.; Campbell, William W. (Muscle & nerve, 2005)
Both high and low body mass index (BMI) have been reported as risk factors for ulnar neuropathy at the elbow (UNE), and a high BMI as a risk factor for carpal tunnel syndrome (CTS). To determine whether the extremes of BMI are risk factors for UNE or CTS, and whether BMI affects calculation of median and ulnar motor nerve conduction velocity (NCV), we retrospectively analyzed the electrodiagnostic records of control patients, UNE patients, and CTS patients. The BMI was calculated for 50 patients with a sole diagnosis of UNE and compared to the BMI of 50 patients with CTS and 50 control subjects. The mean BMIs were 25.9 ± 4.4, 30.1 ± 5.5, and 28.3 ± 5.6 for the UNE, CTS, and controls, respectively. By one‐way analysis of variance, the difference in BMI between the UNE patients and the normal patients was significant (P < 0.01). In the control groups, increasing BMI directly correlated with increasing ulnar motor NCV across the elbow but not with forearm NCV. Across‐elbow (AE) ulnar motor NCV may be falsely increased in patients with a high BMI, probably due to distance measurement factors. Not only do relatively slender individuals have comparatively slower AE ulnar NCVs, they are also at increased risk for developing UNE. Patients with a high BMI are at increased risk for CTS. Muscle Nerve, 2005